26.4k views
0 votes
Evaluate : (r - 3)³ + r² if r = -3 and s = -4. Show all the steps of working for this question.

I have a math test please give me the right answer!!

User Fafl
by
4.9k points

2 Answers

4 votes

Answer:

225

Explanation:

(r - 3)³ + r² if r = -3 and s = -4

(-3 - 3)^3 + (-3)^2

(-6)^3 + (9)

(-6 x -6 x -6) + 9

-216 + 9

-207

User Dkulkarni
by
6.1k points
4 votes

Answer:

-207

Explanation:

Using r= -3, we can substitute r in the whole equation as (-3) which gives you: ((-3)-3)^3 +(-3)^2. Now you can calculate these values in a step by step manner. (-6)^3 +9 then to -216 +9 which brings you to the answer of -207.

User Vedprakash Wagh
by
5.3k points